1998
DOI: 10.1111/j.1439-0507.1998.tb00332.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological study of tinea capitis in schoolchildren in the Nablus area (West Bank)

Abstract: A study of tinea capitis was carried out during the period January-June 1996 in 7525 primary schoolchildren aged 6-14 years comprising 4050 boys and 3475 girls in the Nablus district in the Palestinian area. Fourteen primary schools located in rural, urban and refugee camp areas were surveyed in this study. Seventy-five (1.0%) mycologically proven cases of tinea capitis were detected. The incidence was higher in schools in rural areas (1.9%) than in refugee camps (1.1%) or urban areas (0.4%). Also, the inciden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
9
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 34 publications
10
9
1
Order By: Relevance
“…It was predominant in the youngest age‐group, 0–9 years (2.18%), followed by the 10–19‐year age group (0.87%). Relatively comparable findings (with respect to age‐group variations) were reported in Qatar 23 and in the Nablus area (Palestine) 24 . In tropical Africa, higher rates were reported in Nigerian school children (10.8%) 25…”
Section: Discussionsupporting
confidence: 60%
“…It was predominant in the youngest age‐group, 0–9 years (2.18%), followed by the 10–19‐year age group (0.87%). Relatively comparable findings (with respect to age‐group variations) were reported in Qatar 23 and in the Nablus area (Palestine) 24 . In tropical Africa, higher rates were reported in Nigerian school children (10.8%) 25…”
Section: Discussionsupporting
confidence: 60%
“…However, a comparison of the results on etiological agents of tinea capitis from the current work with those obtained previously from school children from the same area [20, 21], revealed that the anthropophilic dermatophyte T . violaceum continues to be the predominant etiological agent of tinea capitis in the Nablus district (49.8% of total isolates in 1986, 72.6% in 1996, and 82.6% in the present study).…”
Section: Discussionmentioning
confidence: 51%
“…[23] and Ali‐Shtayeh et al. [20], who reported a significant rise in the incidence of infections due toanthropophilic dermatophytes and decreasing importance of zoophilic dermatophytes. The rise of anhropophilic fungi in school children in the study area means that there has been a trend toward more infections transmissible among children, with T .…”
Section: Discussionmentioning
confidence: 99%
“…In many of these countries, schoolchildren and mothers are healthy carriers. The pathogen is common in countries such as Pakistan [9], Kuwait [10], Jordan [11, 12], Saudi Arabia [13, 14] and Turkey [15, 16], and is also reported from Iran [17] and India [18]. In the last 10 years, T. violaceum has reappeared in industrialized countries receiving immigrants from countries in which the fungus is endemic.…”
Section: Discussionmentioning
confidence: 99%